An analysis of sleep and ergometer performance in collegiate male rowers - Babiec, T. (Temple University, 2020)
Introduction: Research has increasingly looked at the effects of sleep on athletic performance. Although there is currently a plethora of data expressing the detrimental effects of sleep deprivation on athletic performance, fewer studies have assessed the effects of sleep extension. Of those studies that have been done, all have been with field or team sport athletes and all have been conducted with athletes who traditionally have practice times later in the day. Rowing is a sport with traditionally early practice times and represents an under examined population. Heart rate variability (HRV) biofeedback has been an increasingly utilized tool in monitoring athletes through training programs and allowing coaches a better picture of the effects of an athlete`s training regimen. Members of the Temple Men`s Rowing Team participated in an eight-week sleep extension study to observe any performance benefits gained from the increased amount of sleep. Methods: Nineteen members of the Temple University`s men`s rowing team were asked to increase their sleep to nine to ten hours a night for four weeks, following a two-week baseline period. A two-week post-intervention phase followed the sleep extension period. Three sport specific assessments (Open rate 1-minute, Rate-capped 1-minute, and Interval tests) and daily HRV recordings were captured each week. Results: Subjects were unable to obtain the amount of sleep for sleep extension, averaging 392.07 ± 53.69 and 374.11 ± 41.53 minutes of total sleep time during baseline and the intervention respectively (p = .137). Significant variation was found in the Interval test and OR1-Min test in a week to week comparison. Conclusion: Athletes failed to increase their time asleep, limiting our ability to assess the impact of sleep on performance. Performance did suffer over the course of the study, suggesting participants were below he minimal amount of sleep necessary to maintain performance. Better athlete education by coaches might prove beneficial for athletes to develop the habits necessary for sufficient sleep and improved performance.